Resin composition, molding material, multilayer structure, molded body, food package, resin composition and method for manufacturing multilayer structure
By adding titanium compounds and sorbic acid to ethylene-modified PVA resin, the thermal stability of PVA resin compositions is significantly enhanced, addressing the limitations of existing PVA resins in heat molding and expanding their application scope.
Patent Information
- Application Number
- JP2024161152
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-19
- Filing Date
- 2024-09-18
- Publication Date
- 2025-04-01
AI Technical Summary
Existing polyvinyl alcohol (PVA) resin compositions face challenges with thermal stability, as their melting point and thermal decomposition temperature are closely related, making heat molding difficult and limiting their applications.
Incorporating a trace amount of titanium compound and sorbic acid and/or its salt into an ethylene-modified PVA resin composition, with specific concentrations of titanium (0.0001 to 2 ppm) and sorbic acid (0.005 to 100 ppm), to enhance thermal stability.
The resulting resin composition exhibits excellent thermal stability, with improved resistance to thermal degradation, allowing for effective heat molding and expanded application possibilities, such as in food packaging.
Smart Images

Figure 2025044182000001 
Figure 2025044182000002
Abstract
Description
[Technical Field]
[0001] The present invention relates to a resin composition containing a polyvinyl alcohol resin, a molding material, a multilayer structure, a resin composition, and a method for producing a multilayer structure. [Background technology]
[0002] Polyvinyl alcohol resin compositions (hereinafter, sometimes referred to as "PVA resins") are one of the few crystalline water-soluble polymers that have excellent film-forming properties, transparency, strength properties, and surface activity. Therefore, they are widely used in applications such as paper coating agents and paper modifiers such as paper internal adhesives, adhesives for paper, wood, and inorganic materials, stabilizers for emulsion polymerization and suspension polymerization, and optical films.
[0003] However, PVA resins generally have problems with thermal stability, such as the melting point and thermal decomposition temperature being very close, making them difficult to mold using hot melt technology, and so they have been used in a water-soluble state.
[0004] Therefore, in order to improve the thermal stability, for example, Patent Document 1 proposes a modified ethylene-vinyl alcohol resin composition containing a modified ethylene-vinyl alcohol resin having 1 to 16.5 mol % of primary hydroxyl group structural units in the side chains and 0.1 to 500 ppm of a conjugated polyene.
[0005] Furthermore, Patent Document 2 proposes a PVA resin having a viscosity average degree of polymerization of a specific amount or more and containing a titanium compound in an amount of 5 to 500 ppm relative to the PVA resin in order to improve moist heat resistance.
[0006] Furthermore, Patent Document 3 proposes a PVA polymer film containing at least one metal element selected from the group consisting of transition metals and aluminum, in order to obtain a PVA polymer film that has excellent slip properties, suppresses the occurrence of wrinkles even when wound into a long film roll, is less likely to be discolored, and has excellent transparency. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] Japanese Patent Publication No. 2023-077420 [Patent Document 2] Japanese Patent Application Publication No. 5-222609 [Patent Document 3] International Publication No. 2013 / 146533 Summary of the Invention [Problem to be solved by the invention]
[0008] According to the investigations of the present inventors, although the technology disclosed in Patent Document 1 has a certain effect on thermal stability, the thermal stability is still insufficient and there is room for improvement.
[0009] Furthermore, the technology disclosed in Patent Document 2 improves moist heat resistance by incorporating 5 to 500 ppm of titanium into the PVA resin, but if the amount is less than 5 ppm, the crosslinking effect is low and high moist heat resistance cannot be obtained.
[0010] Furthermore, the technology disclosed in Patent Document 3 uses an unmodified PVA resin and further contains a titanium compound, but the thermal stability is still insufficient and there is room for improvement.
[0011] Under these circumstances, an object of the present invention is to provide a resin composition having excellent thermal stability. [Means for solving the problem]
[0012] However, in view of the above circumstances, the present inventors have conducted extensive research and have found that a resin composition having excellent thermal stability can be obtained by incorporating a trace amount of a titanium compound and sorbic acid and / or a salt thereof into an ethylene-modified PVA resin.
[0013] That is, the present invention has the following aspects. [1] A resin composition containing a PVA resin, a titanium compound, and sorbic acid and / or a salt thereof, the PVA resin is an ethylene-modified PVA resin containing 1 to 19 mol% of ethylene structural units, A resin composition, wherein the content of the titanium compound in terms of metal is 0.0001 to 2 ppm relative to the mass of the resin composition. [2] The resin composition according to [1], wherein the content of the sorbic acid and / or a salt thereof is 0.005 to 100 ppm relative to the mass of the resin composition. [3] The resin composition according to [1] or [2], wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the resin composition. [4] A molding material comprising the resin composition according to any one of [1] to [3]. [5] A multilayer structure having a layer containing the resin composition according to any one of [1] to [3]. [6] A molded article comprising the multilayer structure according to [5]. [7] A food packaging body comprising the multilayer structure described in [5]. [8] A method for producing the resin composition according to any one of [1] to [3], A method for producing a resin composition, comprising the step of melt-mixing a resin composition raw material containing the PVA resin and the titanium compound. [9] A method for producing the multilayer structure according to [5], A method for producing a multilayer structure, comprising the step of melt-molding a layer containing the resin composition. [Effects of the Invention]
[0014] The resin composition of the present invention has excellent thermal stability. Furthermore, molding materials, molded articles, and food packaging materials containing the resin composition of the present invention, as well as multilayer structures having a layer containing the resin composition of the present invention, also have excellent thermal stability. DETAILED DESCRIPTION OF THE INVENTION
[0015] The present invention will be described below based on examples of embodiments for carrying out the present invention, but the present invention is not limited to the embodiments described below.
[0016] In this specification, "x and / or y (x and y are optional configurations)" means at least one of x and y, and can mean three possibilities: x only, y only, or x and y. When expressed as "X to Y" (X and Y are any numbers), unless otherwise specified, it means "X or more and Y or less," as well as "preferably more than X" or "preferably less than Y." When expressed as "X or more" (X is any number) or "Y or less" (Y is any number), it also means "preferably more than X" or "preferably less than Y." In the present specification, when numerical ranges are described in stages, the upper or lower limit of a certain numerical range can be arbitrarily combined with the upper or lower limit of another numerical range. In addition, in the numerical ranges described in this specification, the upper or lower limit of the numerical range can also be replaced with the values shown in the examples. In this specification, the term "layer" includes not only thick layers but also relatively thin layers such as "films," "tapes," and "sheets."
[0017] <Resin composition> A resin composition according to one embodiment of the present invention (hereinafter sometimes referred to as "the resin composition") contains a PVA resin as the main component and specific trace amounts of a titanium compound and sorbic acid and / or a salt thereof. That is, the base resin of the present resin composition is a PVA resin, and the content of the PVA resin in the present resin composition is usually 70% by mass or more, preferably 80% by mass or more, more preferably 90% by mass or more, and even more preferably 95% by mass or more. Each component will be described below.
[0018] [PVA resin] The PVA resin used in the present embodiment is an ethylene-modified PVA resin having an ethylene structural unit, and is usually obtained by copolymerizing a vinyl ester monomer and ethylene in the presence of a polymerization initiator and then saponifying the copolymer.
[0019] Examples of the vinyl ester monomer include vinyl formate, vinyl acetate, vinyl propionate, vinyl valerate, vinyl caprate, vinyl laurate, vinyl stearate, vinyl benzoate, vinyl pivalate, and vinyl versatate. Among these, vinyl acetate is preferred for obtaining PVA resin. These monomers can be used alone or in combination of two or more. Furthermore, the vinyl ester monomer may be a copolymer of one or more vinyl ester monomers with other monomers copolymerizable therewith. Any conventionally known monomer can be used as the other copolymerizable monomer. The content of the structural unit derived from the other copolymerizable monomer is typically preferably 15 mol % or less, more preferably 10 mol % or less, and even more preferably 5 mol % or less, based on the PVA resin. The vinyl ester monomer may be absent.
[0020] As a polymerization method for copolymerizing the ethylene and the vinyl ester-based monomer in the presence of a polymerization initiator, any known polymerization method can be used, for example, bulk polymerization, solution polymerization, suspension polymerization, emulsion polymerization, etc., but the copolymerization is usually carried out by a bulk polymerization method or a solution polymerization method in which polymerization is carried out without a solvent or in a solvent such as alcohol.
[0021] The alcohol used as a solvent in solution polymerization is usually a lower alcohol such as methanol, ethanol, propanol, etc. These may be used alone or in combination of two or more kinds.
[0022] Examples of the polymerization initiator include known initiators such as azo initiators or peroxide initiators, such as 2,2'-azobisisobutyronitrile, 2,2'-azobis(2,4-dimethyl-valeronitrile), benzoyl peroxide, and n-propyl peroxydicarbonate. The polymerization reaction temperature is selected from the range of 0 to 150°C. These can be used alone or in combination of two or more.
[0023] Saponification can be carried out by a known method, and is usually carried out by dissolving the obtained copolymer in alcohol or dimethyl sulfoxide in the presence of a saponification catalyst. Examples of saponification solvents include methanol, methyl acetate, dimethyl sulfoxide, and dimethylformamide. These can be used alone or in combination of two or more.
[0024] As the saponification catalyst, for example, an alkaline substance such as potassium hydroxide or sodium hydroxide can be used, which can be used alone or in combination of two or more kinds.
[0025] The saponification degree of the PVA resin is usually 90 to 99.99 mol%, preferably 95 to 99.5 mol%, and more preferably 97 to 99 mol%. When the saponification degree is equal to or higher than the lower limit, the PVA resin tends to have better gas barrier properties, thermal stability, moisture resistance, etc. On the other hand, when the saponification degree is equal to or lower than the upper limit, the PVA resin tends to be less susceptible to thermal degradation. The degree of saponification of such a PVA resin can be measured in accordance with JIS K6726.
[0026] The content of ethylene structural units in the PVA resin is usually 1 to 19 mol%, preferably 2 to 15 mol%, and more preferably 3 to 10 mol%. When the content of ethylene structural units is equal to or less than the upper limit, the gas barrier property and thermal stability tend to be excellent. On the other hand, when the content of ethylene structural units is equal to or more than the lower limit, the gas barrier property under high humidity conditions and melt moldability tend to be excellent.
[0027] The content of ethylene structural units in the PVA resin was determined by proton NMR of polyvinyl ester containing ethylene structural units, which is a precursor of the PVA resin. Specifically, the obtained polyvinyl ester was thoroughly purified by reprecipitation with n-hexane / acetone at least three times, and then dried under reduced pressure at 80°C for three days to prepare polyvinyl ester for analysis. The polyvinyl ester was dissolved in DMSO-D and measured at 80°C using a 500 MHz proton NMR (JEOLGX-500). The content of ethylene structural units can be calculated using signals derived from the main-chain methine of the vinyl ester (4.7 to 5.2 ppm) and signals derived from the main-chain methylene of ethylene, vinyl ester, and third component (0.8 to 1.6 ppm).
[0028] The melting point of the PVA resin is usually 100 to 270° C., preferably 120 to 250° C., and more preferably 150 to 230° C. If the melting point is equal to or higher than the lower limit, the resin tends to have excellent heat resistance. On the other hand, if the melting point is equal to or lower than the upper limit, the resin tends to be less susceptible to thermal degradation.
[0029] [Titanium compounds] Examples of the titanium compound used in this embodiment include inorganic titanium compounds and organic titanium compounds. The titanium compounds may be used alone or in combination of two or more. Among these, inorganic titanium compounds are preferred.
[0030] Examples of the inorganic titanium compound include titanium oxide, titanium hydroxide, titanium chloride, and inorganic salts of titanium. Examples of the titanium oxide include titanium oxide (II), titanium oxide (III), titanium oxide (IV), and titanium suboxide. Examples of the titanium hydroxide include titanium(II) hydroxide and titanium(II) hydroxide. Examples of the titanium chloride include titanium(II) chloride and titanium(II) chloride. The inorganic salts of titanium are those other than the titanium chloride, and examples thereof include titanium phosphate and titanium sulfate. Among these, titanium oxide is preferred, titanium(IV) oxide is more preferred, and rutile-type titanium(IV) oxide is particularly preferred.
[0031] Examples of the organic titanium compounds include titanium carboxylates such as titanium acetate, titanium butyrate, and titanium stearate.
[0032] In addition to the case where the titanium compound is present in the resin composition as a titanium compound, the titanium compound may be present in an ionized state or in the form of a complex interacting with a PVA resin or other ligands.
[0033] The average particle size of the titanium compound is usually 0.001 to 100 μm, preferably 0.01 to 50 μm, and more preferably 0.015 to 20 μm. When the average particle size of the titanium compound is within the above range, the thermal stability tends to be further improved. The average particle size here refers to the median diameter.
[0034] The content of the titanium compound in terms of metal is 0.0001 to 2 ppm, preferably 0.0001 to 1 ppm, more preferably 0.001 ppm or more and less than 1 ppm, and even more preferably 0.01 to 0.5 ppm, relative to the mass of the resin composition. When the content of the titanium compound is equal to or greater than the lower limit, the effect of suppressing thermal degradation tends to be excellent, and when the content is equal to or greater than the upper limit, the resin composition tends to be less susceptible to thermal decomposition and coloration.
[0035] The content of the titanium compound in terms of metal can be quantified by measuring the titanium in a constant volume solution obtained by weighing the resin composition into a platinum crucible, ashing it using a burner and an electric furnace, thermally decomposing the ashed material with nitric acid and hydrofluoric acid, treating it with a mixed acid of dilute nitric acid and dilute hydrofluoric acid, and measuring the titanium in the constant volume solution by ICP mass spectrometry using an ICP mass spectrometer (Agilent 8800, manufactured by Agilent Technologies).
[0036] It is speculated that the thermal decomposition of PVA resin is caused by the formation of polyene structures in the main chain due to dehydration reactions initiated by OH groups in the PVA resin under alkaline conditions. Furthermore, in this resin composition, titanium in the titanium compound is stabilized as a tetravalent ion. Therefore, when a polyene structure is formed in the main chain of the PVA resin, it is thought that the titanium compound stabilizes the polyene structure by coordinating with the double bond of the polyene structure to form a chelate. It is speculated that even a trace amount of titanium compound inhibits the further formation of polyene structures.
[0037] [Sorbic acid and / or its salts] Examples of the sorbic acid and / or salts thereof include sorbic acid itself, as well as salts of sorbic acid such as alkali metal salts (e.g., sodium salt, potassium salt, etc.), alkaline earth metal salts (e.g., magnesium salt, calcium salt, strontium salt, barium salt, etc.), transition metal salts, and other metal salts. The sorbic acid and / or salts thereof may be used alone or in combination of two or more.
[0038] Among these sorbic acids and / or salts thereof, those having a carboxy group are preferred because of their high affinity with water, and chain compounds having a carboxy group are more preferred.
[0039] The content of the sorbic acid and / or a salt thereof is usually 0.005 to 100 ppm, preferably 0.01 to 75 ppm, and more preferably 0.1 to 50 ppm, relative to the mass of the resin composition. When the content of the sorbic acid and / or salt thereof is equal to or less than the upper limit, the thermal stability tends to be excellent, and when it is equal to or more than the lower limit, the moldability of the resin composition tends to be excellent.
[0040] The content of sorbic acid and / or a salt thereof can be measured, for example, using a liquid chromatograph-ultraviolet spectrophotometer according to the following procedure. Note that the following procedure will be described using sorbic acid as an example, but other sorbic acids and / or salts thereof can also be measured by the same procedure by using an extraction solvent suitable for the compound. [Method for measuring sorbic acid and / or its salt content] (1) 8 mL of extraction solvent (distilled water:methanol = 1:1, volume ratio) is added to 1 g of powder obtained by freeze-pulverizing the resin composition. (2) This solution is subjected to ultrasonic treatment at 20°C for 1 hour in a static state to extract the sorbic acid from the resin, and after cooling, the solution is adjusted to a constant volume of 10 mL with the extraction solvent. It may also be diluted to any desired ratio as needed. (3) After filtering the solution through a filter with a pore size of 0.45 μm, the amount of sorbic acid in the extracted solution is measured using a liquid chromatograph-ultraviolet spectrophotometer. (4) A calibration curve is prepared from the standard solution of sorbic acid prepared using the above extraction solvent, and the sorbic acid content is quantified by the absolute calibration curve method. [HPLC measurement conditions] LC system: Agilent 1260 / 1290 [Agilent Technologies] Detector: Agilent 1260 infinity diode array detector [Agilent Technologies] Column: Cadenza CD-C18 (100 x 3.0 mm, 3 μm) [Imtakt] Column temperature: 40℃ Mobile phase A: 5% acetonitrile in water containing 0.05% formic acid Mobile phase B: 95% acetonitrile in water containing 0.05% formic acid Time Program: 0.0 → 5.0 minutes B% = 30% 5.0→8.0 minutes B%=30%→50% 8.0→10.0 minutes B%=50% 10.0→13.0 minutes B%=50%→30% 13.0→15.0 minutes B%=30% ·Flow rate: 0.2mL / min UV detection wavelength: 190~400nm ·Quantitation wavelength: 262nm In the HPLC measurement conditions, "%" means volume %.
[0041] The mass ratio of the content of the sorbic acid and / or a salt thereof to the content of the titanium compound converted into metal is preferably 0.0025 to 1,000,000, more preferably 0.05 to 50,000, and particularly preferably 10 to 1,000. When the mass ratio is equal to or less than the upper limit, the thermal stability tends to be excellent, and when the mass ratio is equal to or more than the lower limit, the moldability of the resin composition tends to be excellent.
[0042] The reason why excellent effects can be obtained by combining appropriate amounts of the titanium compound and the sorbic acid and / or its salt is not clear, but it is presumed that the combined use of a specific amount of the titanium compound and the sorbic acid and / or its salt reduces the pH appropriately, strengthening the hydrogen bonds in the hydroxyl groups of the PVA resin and thereby improving thermal stability.
[0043] [Other thermoplastic resins] The present resin composition may contain a thermoplastic resin other than PVA resin within a range that does not impair the effects of the present invention (for example, typically 30% by mass or less of the present resin composition, preferably 20% by mass or less, particularly preferably 10% by mass or less, the lower limit being typically 0% by mass). As the other thermoplastic resin, known thermoplastic resins can be used, such as polyester resins, polystyrene resins, polyvinyl chloride resins, polycarbonate resins, ionomers, polyvinylidene chloride, polyester elastomers, polyurethane elastomers, chlorinated polyethylene, chlorinated polypropylene, etc. These can be used alone or in combination of two or more.
[0044] [Other compounding agents] The resin composition may also contain additives generally incorporated into PVA resins (excluding titanium compounds and sorbic acid and / or its salts) within a range that does not impair the effects of the present invention (for example, typically 30% by mass or less of the resin composition, preferably 20% by mass or less, particularly preferably 10% by mass or less, the lower limit being typically 0% by mass). Examples of such additives include inorganic double salts (e.g., hydrotalcite), plasticizers (e.g., aliphatic polyhydric alcohols such as ethylene glycol, glycerin, and hexanediol), oxygen absorbers (e.g., inorganic oxygen absorbers such as aluminum powder and potassium sulfite; ascorbic acid, its fatty acid esters and metal salts; gallic acid; polyhydric phenols such as hydroxyl group-containing phenolaldehyde resins; terpene compounds; blends of tertiary hydrogen-containing resins and transition metals (e.g., a combination of polypropylene and cobalt); and resins containing carbon-carbon unsaturated bonds. The composition may also contain polymeric oxygen absorbers such as blends with transition metals (e.g., a combination of polybutadiene and cobalt), photooxidatively degradable resins (e.g., polyketones), anthraquinone polymers (e.g., polyvinyl anthraquinone), and mixtures thereof to which photoinitiators (e.g., benzophenone) or antioxidants or deodorizers (e.g., activated carbon) other than those mentioned above, heat stabilizers, light stabilizers, ultraviolet absorbers, colorants, antistatic agents, surfactants (excluding those used as lubricants), antibacterial agents, antiblocking agents, fillers (e.g., inorganic fillers), etc. These compounds may be used alone or in combination of two or more.
[0045] [Method for producing resin composition] The resin composition can be produced by mixing the PVA resin, titanium compound, and sorbic acid and / or a salt thereof by a known method such as dry blending, melt mixing, solution mixing, impregnation, etc. Among these, it is preferable to produce the resin composition by a method including a step of melt mixing the resin composition raw materials containing the PVA resin and titanium compound. Furthermore, these production methods can be arbitrarily combined.
[0046] The dry blending method may be, for example, (i) a method in which a pellet-shaped PVA resin, sorbic acid and / or a salt thereof, and a titanium compound are dry-blended using a tumbler or the like.
[0047] Examples of the melt mixing method include (ii) a method in which a pellet-shaped PVA resin is dry-blended with sorbic acid and / or a salt thereof, and a titanium compound, and the dry blend is melt-kneaded; and (iii) a method in which sorbic acid and / or a salt thereof, and a titanium compound are added to a molten PVA resin, and the mixture is melt-kneaded.
[0048] Examples of the solution mixing method include (iv) a method in which a solution is prepared using a commercially available PVA resin, and sorbic acid and / or a salt thereof and a titanium compound are blended therein, followed by coagulation and molding, followed by solid-liquid separation and drying by known means; and (v) a method in which, during the production process of a PVA resin, sorbic acid and / or a salt thereof and a titanium compound are added to an ethylene-vinyl ester copolymer solution before saponification or a homogeneous solution of a PVA resin (such as a water / alcohol solution), followed by coagulation and molding, followed by solid-liquid separation and drying by known means.
[0049] The impregnation method includes, for example, (vi) a method in which pelletized PVA resin is brought into contact with an aqueous solution containing sorbic acid and / or a salt thereof, and a titanium compound, so that the sorbic acid and / or a salt thereof, and the titanium compound are contained in the PVA resin, and then the PVA resin is dried. The aqueous solution containing the titanium compound may be an aqueous solution of the titanium compound or a titanium compound immersed in water containing various chemicals to elute titanium ions. In the impregnation method, the content of sorbic acid and / or its salt and the content of titanium compound (in terms of metal) can be controlled by the concentration of sorbic acid and / or its salt and titanium compound in the aqueous solution in which the PVA resin is immersed, the immersion temperature, the immersion time, etc. The immersion temperature and immersion time are usually 0.5 to 48 hours, preferably 1 to 36 hours, and the immersion temperature is usually 10 to 40°C, preferably 20 to 35°C.
[0050] As the drying method in each of the above-mentioned production methods, various drying methods can be used, and either static drying or fluidized drying may be used, or these may be used in combination.
[0051] As mentioned above, in the present invention, the above-mentioned different methods can be combined. Among them, the melt mixing method is preferred, and method (ii) is particularly preferred, in terms of productivity and the fact that a resin composition can be obtained in which the effects of the present invention are more pronounced. Furthermore, when using the other thermoplastic resins and other compounding agents, they may be compounded by a conventional method according to the above-mentioned production method.
[0052] The resin composition obtained by each of the above-mentioned production methods may be in any shape, but is preferably in the form of pellets. The pellets may be spherical, oval, cylindrical, cubic, rectangular, or the like, but are usually oval or cylindrical. From the viewpoint of convenience when used later as a molding material, the size of the pellets is such that, in the case of an oval shape, the minor axis is usually 1 to 10 mm, preferably 2 to 6 mm, and even more preferably 2.5 to 5.5 mm, and the major axis is usually 1.5 to 30 mm, preferably 3 to 20 mm, and even more preferably 3.5 to 10 mm. In the case of a cylindrical shape, the diameter of the base is usually 1 to 6 mm, preferably 2 to 5 mm, and the length is usually 1 to 6 mm, preferably 2 to 5 mm. Moreover, it is preferable that the shape and size of the pellet-shaped PVA resin used in each of the above-mentioned production methods are similar.
[0053] The water content of the present resin composition is usually 0.01 to 0.5% by mass, preferably 0.05 to 0.35% by mass, and more preferably 0.1 to 0.3% by mass.
[0054] The water content of the resin composition is measured and calculated by the following method. The mass (W1) of this resin composition before drying is weighed on an electronic balance, dried in a hot air dryer at 150°C for 5 hours, and then left to cool in a desiccator for 30 minutes, after which the mass (W2) is weighed and calculated using the following formula. Moisture content (mass%)=[(W1-W2) / W1]×100
[0055] When the resin composition is in the form of pellets, it is also preferable to apply a known lubricant to the surface of the pellets to stabilize the feedability during melt molding. Examples of lubricants include higher fatty acids having 12 or more carbon atoms (e.g., lauric acid, myristic acid, palmitic acid, stearic acid, behenic acid, oleic acid, etc.), higher fatty acid esters (methyl esters, isopropyl esters, butyl esters, octyl esters of higher fatty acids, etc.), higher fatty acid amides (e.g., saturated higher fatty acid amides such as lauric acid amide, myristic acid amide, palmitic acid amide, stearic acid amide, behenic acid amide, etc.; unsaturated higher fatty acid amides such as oleic acid amide, erucic acid amide, etc.; bis-higher fatty acid amides such as ethylene bisstearic acid amide, ethylene bisoleic acid amide, ethylene biserucic acid amide, ethylene bislauric acid amide, etc.), low-molecular-weight polyolefins (e.g., low-molecular-weight polyethylene or low-molecular-weight polypropylene having a molecular weight of about 500 to 10,000, or acid-modified products thereof), higher alcohols having 6 or more carbon atoms, ester oligomers, and fluorinated ethylene resins. These compounds may be used alone or in combination of two or more. The content of such lubricants in the resin composition is usually 5% by mass or less, preferably 1% by mass or less. The lower limit is usually 0% by mass.
[0056] The resin composition thus obtained can suppress thermal degradation when heated, and the temperature (°C) at which the resin composition loses 40% by mass is usually 391°C or higher, preferably 393°C or higher, and more preferably 395°C or higher. The higher the temperature (°C) at which a 40% mass reduction occurs, the better, but the upper limit is usually 550°C.
[0057] The temperature (°C) at which the resin composition loses 5% by mass is usually higher than 336°C, and preferably 340°C or higher. The upper limit of the temperature (°C) at which a 5% mass reduction occurs is preferably as high as possible, but is usually 550°C. A difference of 1°C in the temperature at which the mass is reduced results in a large difference in yield in actual production, and therefore the difference is very large.
[0058] The "temperature (°C) at 40% mass reduction" and "temperature (°C) at 5% mass reduction" can be measured using a thermogravimetric analyzer, for example, by the method described in the Examples below.
[0059] [Molding material] The resin composition thus obtained is prepared into various forms, such as pellets, powder, or liquid, and is provided as a molding material for various molded articles. In particular, in the present invention, when it is provided as a material for melt molding, the effects of the present invention tend to be more efficiently obtained, which is preferable. The present resin composition also includes resin compositions obtained by mixing resins other than the PVA resin used in the present resin composition.
[0060] Examples of the molded article include a single layer film molded from the present resin composition, as well as a multilayer structure having at least one layer containing the present resin composition.
[0061] [Multilayer structure] A multilayer structure according to one embodiment of the present invention (hereinafter referred to as "the multilayer structure") has a layer containing the present resin composition. The layer made of the present resin composition (hereinafter simply referred to as "the present resin composition layer") can be laminated with another substrate (hereinafter the resin used in the substrate may be abbreviated as "substrate resin") whose main component is a thermoplastic resin other than the present resin composition to impart additional strength, protect the present resin composition layer from the effects of moisture, etc., or impart other functions.
[0062] Examples of the base resin include polyethylene-based resins such as linear low-density polyethylene, low-density polyethylene, very low-density polyethylene, medium-density polyethylene, high-density polyethylene, ethylene-propylene (block and random) copolymers, and ethylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; polypropylene-based resins such as polypropylene and propylene-α-olefin (α-olefin having 4 to 20 carbon atoms) copolymers; (unmodified) polyolefin-based resins such as polybutene, polypentene, and polycyclic olefin-based resins (polymers having a cyclic olefin structure in at least one of the main chain and side chain); and polyolefins obtained by dissolving these polyolefins in an unsaturated carboxylic acid or its derivatives. Examples of the polyolefin resin include polyolefin resins in the broad sense, including modified olefin resins such as unsaturated carboxylic acid-modified polyolefin resins graft-modified with an ester of the above, ionomers, ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, ethylene-acrylic acid ester copolymers, polyester resins, polyamide resins (including copolymerized polyamides), polyvinyl chloride, polyvinylidene chloride, acrylic resins, polystyrene resins, vinyl ester resins, polyester elastomers, polyurethane elastomers, polystyrene elastomers, halogenated polyolefins such as chlorinated polyethylene and chlorinated polypropylene, aromatic or aliphatic polyketones, etc. These may be used alone or in combination of two or more. The terms linear low density polyethylene, low density polyethylene, very low density polyethylene, medium density polyethylene, and high density polyethylene are commonly used to represent types of polyethylene.
[0063] Among these, hydrophobic resins such as polyamide-based resins, polyolefin-based resins, polyester-based resins, and polystyrene-based resins are preferred, and more preferred are polyolefin-based resins such as polyethylene-based resins, polypropylene-based resins, polycyclic olefin-based resins, and unsaturated carboxylic acid-modified polyolefin-based resins thereof.
[0064] The layer structure of the present multilayer structure can be any combination, such as a / b, b / a / b, a / b / a, a1 / a2 / b, a / b1 / b2, b2 / b1 / a / b1 / b2, or b2 / b1 / a / b1 / a / b1 / b2, where a (a1, a2, ...) represents the resin composition layer and b (b1, b2, ...) represents the base resin layer. Furthermore, when R represents a recycled layer containing a mixture of the present resin composition and a thermoplastic resin other than the present resin composition, obtained by remelting and molding edges or defective products generated during the manufacturing process of the present multilayer structure, the layer structure can be b / R / a, b / R / a / b, b / R / a / R / b, b / a / R / a / b, b / R / a / R / a / R / b, or b / R / a / R / a / R / b. The total number of layers in the present multilayer structure is usually 2 to 15, preferably 3 to 10. In the above layer structure, an adhesive resin layer containing an adhesive resin may be interposed between the respective layers, if necessary.
[0065] Known adhesive resins can be used, and may be selected appropriately depending on the type of thermoplastic resin used in the base resin layer "b." Representative examples include modified polyolefin polymers containing carboxy groups, which are obtained by chemically bonding an unsaturated carboxylic acid or its anhydride to a polyolefin resin through an addition reaction, a graft reaction, or the like. Examples of modified polyolefin polymers containing carboxy groups include maleic anhydride-grafted polyethylene, maleic anhydride-grafted polypropylene, maleic anhydride-grafted ethylene-propylene (block and random) copolymers, maleic anhydride-grafted ethylene-ethyl acrylate copolymers, maleic anhydride-grafted ethylene-vinyl acetate copolymers, maleic anhydride-grafted polycyclic olefin resins, and maleic anhydride-grafted polyolefin resins. These may be used alone or in combination of two or more.
[0066] In the present multilayer structure, when an adhesive resin layer is used between the present resin composition layer and the base resin layer, since the adhesive resin layers are located on both sides of the present resin composition layer, it is preferable to use an adhesive resin with excellent hydrophobicity.
[0067] The base resin and adhesive resin may contain conventionally known plasticizers, fillers, clays (montmorillonite, etc.), colorants, antioxidants, antistatic agents, lubricants, core materials, antiblocking agents, waxes, etc., within the range that does not impair the spirit of the present invention (for example, 30% by mass or less, preferably 10% by mass or less, based on the total resin). These may be used alone or in combination of two or more.
[0068] The lamination of the resin composition layer and the substrate resin layer (including the case where an adhesive resin layer is interposed) can be performed by a known method. Examples include a method of melt-extrusion laminating the substrate resin onto a film, sheet, etc. of the resin composition, a method of melt-extrusion laminating the resin composition onto a substrate resin layer, a method of co-extruding the resin composition and the substrate resin, a method of dry-laminating the resin composition (the resin composition layer) and the substrate resin (the substrate resin layer) using a known adhesive such as an organic titanium compound, an isocyanate compound, a polyester compound, or a polyurethane compound, and a method of applying a solution of the resin composition onto the substrate resin and then removing the solvent. Among these, from the viewpoints of cost and environment, it is preferable to produce the resin composition by including a step of melt-molding the resin composition layer, and specifically, a co-extrusion method is preferred.
[0069] The multilayer structure may be subjected to a (heat) stretching treatment, if necessary. The stretching treatment may be either uniaxial stretching or biaxial stretching, and in the case of biaxial stretching, it may be simultaneous stretching or sequential stretching. Furthermore, the stretching method may be a roll stretching method, tenter stretching method, tubular stretching method, stretch-blow method, vacuum pressure forming, or the like, whichever provides a higher stretch ratio. The stretching temperature is a temperature near the melting point of the multilayer structure, and is usually selected from the range of 40 to 170°C, preferably about 60 to 160°C. When the stretching temperature is equal to or higher than the lower limit, the stretchability tends to be excellent, and when it is equal to or lower than the upper limit, a stable stretched state tends to be maintained.
[0070] The stretched multilayer structure may be heat-set to provide dimensional stability. Heat setting can be performed by known means, for example, by heat-treating the stretched multilayer structure while maintaining tension at typically 80 to 180°C, preferably 100 to 165°C, for typically 2 to 600 seconds.
[0071] When the stretched multilayer structure is to be used as a shrink film, the heat-shrinkability can be imparted to the multilayer structure by, for example, cooling and fixing the multilayer structure by applying cold air thereto, without carrying out the heat-setting process described above.
[0072] The thickness of the present multilayer structure (including a stretched one), and further the thickness of the present resin composition layer, substrate resin layer, and adhesive resin layer that constitute the multilayer structure, cannot be generalized depending on the layer configuration, type of substrate resin, type of adhesive resin, intended use, packaging form, required physical properties, etc., but the thickness of the present multilayer structure (including a stretched one) is usually 10 to 5,000 μm, preferably 30 to 3,000 μm, and more preferably 50 to 2,000 μm. The present resin composition layer is usually 1 to 500 μm, preferably 3 to 300 μm, and more preferably 5 to 200 μm. The substrate resin layer is usually 5 to 3,000 μm, preferably 10 to 2,000 μm, and particularly preferably 20 to 1,000 μm. The adhesive resin layer is usually 0.5 to 250 μm, preferably 1 to 150 μm, and more preferably 3 to 100 μm.
[0073] Furthermore, the thickness ratio of the present resin composition layer to the base resin layer in the present multilayer structure (present resin composition layer / base resin layer), when there are multiple layers, is typically 1 / 99 to 50 / 50, preferably 5 / 95 to 45 / 55, and more preferably 10 / 90 to 40 / 60, and when there are multiple layers, the thickness ratio of the present resin composition layer to the adhesive resin layer (present resin composition layer / adhesive resin layer), when there are multiple layers, is typically 10 / 90 to 99 / 1, preferably 20 / 80 to 95 / 5, and more preferably 50 / 50 to 90 / 10.
[0074] This multilayer structure can also be used to produce cup- or tray-shaped molded articles and food packaging. In these cases, a drawing method is typically used, specifically vacuum forming, pressure forming, vacuum-pressure forming, plug-assisted vacuum-pressure forming, etc. Furthermore, blow molding is used to produce tube- or bottle-shaped multilayer containers (laminate structure) from a multilayer parison (a hollow tubular preform before blowing). Specific examples include extrusion blow molding (two-head, mold-moving, parison-shift, rotary, accumulator, horizontal parison, etc.), cold parison blow molding, injection blow molding, and biaxial stretch blow molding (extrusion-type cold parison biaxial stretch blow molding, injection-type cold parison biaxial stretch blow molding, injection-molding in-line biaxial stretch blow molding, etc.). The resulting laminate may be subjected to heat treatment, cooling treatment, rolling treatment, printing treatment, dry lamination treatment, solution or melt coating treatment, bag making, deep drawing, box processing, tube processing, splitting processing, etc. as required. [Example]
[0075] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following examples as long as it does not depart from the gist of the invention. In the examples, "parts" and "%" are by mass.
[0076] Prior to the examples, the following ingredients were prepared: Ethylenic PVA resin: Ethylene-modified PVA resin pellets with an ethylene structural unit content of 4 mol%, a melting point of 213°C, and a saponification degree of 98 mol% Titanium compound: Rutile-type titanium(IV) oxide with an average particle size of 5 μm or less (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) Sorbic acid and / or its salts: Sorbic acid (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.)
[0077] Example 1 The ethylene-modified PVA resin pellets were dry-blended with the sorbic acid so that the sorbic acid was 50 ppm relative to the mass of the resin composition, and the titanium oxide was 0.1 ppm relative to the mass of the resin composition in terms of metal, to obtain a mixture. The mixture was then fed into a twin-screw extruder (20 mmφ) equipped with a two-hole die, extruded under the following extrusion conditions, and the extruded strands were cooled and solidified by air cooling. The solidified strands were then cut using a pelletizer to obtain pellets of the resin composition.
[0078] [Extrusion conditions] Extruder setting temperature (℃): C1 / C2 / C3 / C4 / C5 / C6 =200 / 210 / 225 / 225 / 225 / 225
[0079] <Example 2> Pellets of a resin composition were obtained in the same manner as in Example 1, except that the titanium oxide content, calculated as metal, was changed to 1 ppm relative to the mass of the resin composition.
[0080] <Comparative Example 1> Pellets of a resin composition were obtained in the same manner as in Example 1, except that titanium oxide was not used.
[0081] <Comparative Example 2> Pellets of a resin composition were obtained in the same manner as in Example 1, except that the titanium oxide content was changed to 10 ppm in terms of metal relative to the mass of the resin composition.
[0082] <Comparative Example 3> Pellets of a resin composition were obtained in the same manner as in Example 2, except that sorbic acid was not used.
[0083] The following temperature at 40% reduction was measured using the obtained pellets of the resin compositions of Examples 1 and 2 and Comparative Examples 1 to 3. The results are shown in Table 1 below.
[0084] [Temperature at 40% reduction] Using 5 mg of pellets of the obtained resin composition, the weight change was measured using a thermogravimetric analyzer (Pyris 1 TGA, manufactured by Perki Elmer) under conditions of an air flow rate of 20 mL / min, a heating rate of 10°C / min, and a temperature range of 30 to 550°C, and the temperatures at which the weight decreased by 40% were compared. A higher temperature at which the weight decreased by 40% indicates better thermal stability of the resin composition. The evaluation was carried out based on the following criteria. A (good): 393°C or higher B (average): 390℃ or higher and less than 393℃ C(poor): Less than 390℃
[0085] [Temperature at 5% decrease] Furthermore, using 5 mg of pellets of the resin compositions obtained in Examples 1 and 2, the temperature (°C) at 5% loss was measured using a thermogravimetric analyzer (Pyris 1 TGA, manufactured by Perki Elmer) under conditions of an air flow rate of 20 mL / min, a heating rate of 10°C / min, and a temperature range of 30 to 550°C in a nitrogen atmosphere. A higher temperature (°C) at 5% loss indicates better thermal stability of the resin composition. The evaluation was carried out based on the following criteria, and the results are shown in Table 2. AA(excellent): 341℃ or higher A (good): 336℃ or higher and less than 341℃ B (average): Less than 336°C
[0086] [Table 1]
[0087] [Table 2]
[0088] As can be seen from Tables 1 and 2, the resin compositions of Examples 1 and 2, which contain an ethylene-modified PVA resin, sorbic acid and / or a salt thereof, and a specific amount of a titanium compound, have superior thermal stability compared to the resin composition of Comparative Example 1, which does not contain a titanium compound; the resin composition of Comparative Example 2, which contains a titanium compound in an amount greater than the specific range; and the resin composition of Comparative Example 3, which does not contain sorbic acid and / or a salt thereof. The multilayer structures including layers made of the resin compositions of Examples 1 and 2 also have excellent thermal stability. [Industrial Applicability]
[0089] The present resin composition has an improved thermal decomposition temperature during melt molding and is excellent in thermal stability and gas barrier properties. Therefore, it is useful as a packaging material for various foods, as well as seasonings such as mayonnaise and dressings, fermented foods such as miso, oily foods such as salad oil, beverages, cosmetics, medical products, etc., and as a material for molded products for packaging pesticides, detergents, civil engineering additives, disinfectants, dyes, pigments, etc.
Claims
1. A resin composition containing a polyvinyl alcohol resin, a titanium compound, and sorbic acid and / or a salt thereof, the polyvinyl alcohol resin is an ethylene-modified polyvinyl alcohol resin containing 1 to 19 mol % of ethylene structural units, The resin composition has a titanium compound content of 0.0001 to 2 ppm in terms of metal based on the mass of the resin composition.
2. The resin composition according to claim 1, wherein the content of the sorbic acid and / or a salt thereof is 0.005 to 100 ppm based on the mass of the resin composition.
3. 3. The resin composition according to claim 1, wherein the content of the titanium compound in terms of metal is 0.0001 ppm or more and less than 1 ppm based on the mass of the resin composition.
4. A molding material comprising the resin composition according to claim 1 or 2.
5. A multilayer structure having a layer comprising the resin composition according to claim 1 or 2.
6. A molded article comprising the multilayer structure according to claim 5 .
7. A food package comprising the multi-layer structure of claim 5.
8. A method for producing the resin composition according to claim 1 or 2, A method for producing a resin composition, comprising: melt-mixing a resin composition raw material containing the polyvinyl alcohol resin and the titanium compound.
9. A method for producing the multi-layer structure of claim 5, comprising the steps of: A method for producing a multilayer structure, comprising: melt-molding a layer containing the resin composition.
Citation Information
Patent Citations
Polyvinyl alcohol fiber and its production
JP1993222609A
Modified ethylene-vinyl alcohol-based resin composition, and gas barrier material
JP2023077420A
Polyvinyl alcohol-type polymer film and method for producing same
WO2013146533A1